ANALYSIS OF NEWS PORTAL DISCUSSION 'WAYANG ORANG PENGET' DELIGHTS MALANG THEATERGOERS ON JAKARTA POST - Simanjuntak, Anni Alvionita (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2022)
Objective Critical discourse analysis is always interesting to study more deeply. The power of the media and public perceptions that make critical discourse research continue to grow. This helps readers understand the use of language because language is not just a means of communication, but is also used as an instrument to do something. Materials and Methods. The formulation of the problem of this research is how the critical discourse analysis of the van Dijk model is in the Jakarta Post 'Wayang Orang Penget' Delights Malang Theatergoers. This type of research is qualitative research because the data studied is news that has been transcribed. Data collection techniques in this study use observation and documentation techniques. Result. The results of the study show that in the reporting of